Women, the unsung heroes of rangeland management in Arbahajan Ward, Wajir County, Kenya - Mukalo, Irene (International Livestock Research Institute, 2024)
With CGIAR Research Initiative on Livestock and Climate, AICCRA and partners are building capacities in Kenya for participatory rangeland management (PRM), resulting in significant impacts in good governance, including women's participation and community commitment to restoring lands.